Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1108/17542411111116563
|View full text |Cite
|
Sign up to set email alerts
|

Leadership attributes, masculinity and risk taking as predictors of crisis proneness

Abstract: PurposeThe purpose of this paper is to examine the extent to which leadership attributes, masculinity, risk taking and decision making affect perceived crisis proneness.Design/methodology/approachThe paper draws mainly on the literature about gender, leadership and organizational crisis to explore whether masculinity predicts crisis proneness, and the extent to which leadership attributes as well as risk‐taking and decision‐making style are efficient predictors of perceived crisis preparedness (CP). Utilizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 111 publications
0
26
0
Order By: Relevance
“…For example, despite observations such as Ibarra and Hansen's (2009) that women are twice as likely as men to be appointed from outside the company our results suggest that without sufficient representation of women on the board, even a policy of outside promotion is unlikely to result in more female CEOs. In terms of gender and risk taking (examined in general in Sheaffer et al, 2011;Maxfield et al, 2010;Beckmann and Menkoff, 2008), the only factor analyzed in our study of risk taking by newly appointed female CEOs, that rivals gender for statistical significance is profitability (measured as industry adjusted ROA). It is reasonable to expect that firms consider their degree of profitability when establishing the risk profile of the firm.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, despite observations such as Ibarra and Hansen's (2009) that women are twice as likely as men to be appointed from outside the company our results suggest that without sufficient representation of women on the board, even a policy of outside promotion is unlikely to result in more female CEOs. In terms of gender and risk taking (examined in general in Sheaffer et al, 2011;Maxfield et al, 2010;Beckmann and Menkoff, 2008), the only factor analyzed in our study of risk taking by newly appointed female CEOs, that rivals gender for statistical significance is profitability (measured as industry adjusted ROA). It is reasonable to expect that firms consider their degree of profitability when establishing the risk profile of the firm.…”
Section: Discussion Implications and Conclusionmentioning
confidence: 99%
“…We also address the question of risk taking by female CEOs. The relation between gender and risk taking is an empirical issue, but the two have often been thought of as linked (Sheaffer et al, 2011;Maxfield et al, 2010;Beckmann and Menkoff, 2008). Some of these studies involve risk taking as revealed by questionnaires, simulations or experiments (Maxfield et al, 2010).…”
mentioning
confidence: 99%
“…Sheaffer et al . () found a link between masculine traits, crisis proneness and noticeable risk taking among leaders. While domination of females in the nursing workforce is acknowledged (AIHW ), little emphasis is evident on the influence of gender on clinical leadership effectiveness in nursing.…”
Section: Discussionmentioning
confidence: 98%
“…While the literature highlights the technical/business ability to strategize and develop a vision (Appelbaum et al, 2013), most of the skills typically required from those at the top are "soft skills", such as adaptability and acquisition of novel knowledge, skills and capabilities (Ellemers et al, 2012); communication of performance (Grant and Taylor, 2014;Ibarra and Obodaru, 2009;Ibarra and Sackley, 2011); leadership (Sheaffer et al, 2011); negotiation (Hawley, 2014); and networking skills (Brands and Kilduff, 2014).…”
Section: Challenge 2: Advancement and Promotionmentioning
confidence: 99%